2012
DOI: 10.1007/s00441-011-1316-1
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell-based tissue engineering in veterinary orthopaedics

Abstract: Regenerative medicine is one of the most intensively researched medical branches, with enormous progress every year. When it comes to translating research from bench to bedside, many of the pioneering innovations are achieved by cooperating teams of human and veterinary medical scientists. The veterinary profession has an important role to play in this new and evolving technology, holding a great scientific potential, because animals serve widely as models for human medicine and results obtained from animals m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 114 publications
(140 reference statements)
0
17
0
1
Order By: Relevance
“…1 Recently, various applications of tissue engineering have been reported in veterinary medicine. 2,3 One of the main difficulties in tissue engineering is that the vascularization of the engineered tissues is inevitable. Previous studies 4,5 reveal that vascularization in engineered tissues with mature endothelial cells improves blood perfusion, cell viability, and survival of the tissues after transplantation.…”
mentioning
confidence: 99%
“…1 Recently, various applications of tissue engineering have been reported in veterinary medicine. 2,3 One of the main difficulties in tissue engineering is that the vascularization of the engineered tissues is inevitable. Previous studies 4,5 reveal that vascularization in engineered tissues with mature endothelial cells improves blood perfusion, cell viability, and survival of the tissues after transplantation.…”
mentioning
confidence: 99%
“…The positive and negative pre-clinical results are to be published and made available to patients and public. These TEMPs can be tested in various general veterinary medical hospitals with due animal ethics approvals as pre-clinical results and an opportunity to upgrade the veterinary clinical medicine [35] . Pre-clinical studies provides the basic toxicity profiles, enables to identify the active dose levels, adverse events, supports trial eligibility criteria, and enables to identify the critical clinical parameters, risk benefit criteria.…”
Section: Regulations For Innovative Tempsmentioning
confidence: 99%
“…In horses, a few preliminary experiments have been performed in which a pastern joint arthrodesis was supported by a combined therapy of stem cells and a bone replacement material, resulting in an adequate development of bone fusion (Brehm et al 2012). However, controlled clinical studies on the application of MSC in bone regeneration in horses have not yet been reported.…”
Section: Months No Significant Effectmentioning
confidence: 99%